Nonlinear forced vibration analysis of spinning shaft‐disk assemblies under sliding bearing supports. (7th January 2021) - Zhao, Tian Yu; Wang, Yu Xuan; Pan, Hong Gang; Yuan, Hui Qun; Cai, Yi
Abstract : This paper presents an investigation on nonlinear forced vibration characteristics of a spinning shaft‐disk assembly resting on sliding bearing supports. Based on the Timoshenko beam theory and Kirchhoff plate theory, the coupled model of the rotor is established. The present model is validated through comparison with the experiment results for different structure parameters. Considering the gyroscopic effect and nonlinear oil film force, the equations of motion are derived by employing the Lagrange equation. Then, the modal synthesis method and the Runge‐Kutta method are adopted to obtain forced vibration responses of the spinning assembly. Special attention is paid to examine the effect of spinning speed on the nonlinear vibration behaviors of the shaft‐disk rotor system, which can play an especially important role in an actual project.